Worlds together, worlds apart - Tignor, Robert (W.W. Norton, 2008)
11 chapters: Ecoming Human; rivers, cities and first states, 4000 - 2000 BCE; Nomads, territorial states, and microsocieties, 2000 - 1200 BCE; first empires and common cultures in afro - eurasia, 1200-350 BCE; world turned inside out, 1000-350 BCE,...; Includes bibliographical references and index